2018
DOI: 10.1111/jcmm.13982
|View full text |Cite
|
Sign up to set email alerts
|

High proportion of transient neonatal zinc deficiency causing alleles in the general population

Abstract: Loss of function (LoF) mutations in the zinc transporter SLC30A2/ZnT2 result in impaired zinc secretion into breast milk consequently causing transient neonatal zinc deficiency (TNZD) in exclusively breastfed infants. However, the frequency of TNZD causing alleles in the general population is yet unknown. Herein, we investigated 115 missense SLC30A2/ZnT2 mutations from the ExAC database, equally distributed in the entire coding region, harboured in 668 alleles in 60 706 healthy individuals of diverse ethnicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…ZnT2 was previously shown [9,21,44] to mediate the accumulation of zinc in intracellular vesicles in MCF-7 cells as indicated by the specific zinc probe FluoZin3 (Fig 6A). Furthermore, ZnT2 was previously shown to play a role in lysosomal zinc accumulation in both mouse mammary gland cells and in human HeLa cells [15,45,46].…”
Section: Resultsmentioning
confidence: 66%
“…ZnT2 was previously shown [9,21,44] to mediate the accumulation of zinc in intracellular vesicles in MCF-7 cells as indicated by the specific zinc probe FluoZin3 (Fig 6A). Furthermore, ZnT2 was previously shown to play a role in lysosomal zinc accumulation in both mouse mammary gland cells and in human HeLa cells [15,45,46].…”
Section: Resultsmentioning
confidence: 66%
“…While to our knowledge ZnT heterodimerization has only been shown in transfected cell systems, these studies suggest an intriguing level of zinc transporter complementation that needs further exploration. Moreover, the idea that variants in ZnT2 may alter heterodimer location and function is an additional avenue that warrants investigation, given how common non-synonymous variants in ZnT2 are in the population 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In humans, seven missense mutations have thus far been identified in SLC30A2 that are associated with a 50–90% reduction in milk zinc concentration and result in severe neonatal zinc deficiency in exclusively breastfed infants 1821 . However, ZnT2 variants are likely quite common, as Golan and colleagues recently estimated the frequency of loss-of-function mutations to be 1 in 2334 22 . Indeed, we recently reported that non-synonymous ZnT2 variants are quite common in humans; 36% of a random population of breastfeeding women harbored non-synonymous ZnT2 variants.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently proposed that a haploinsufficiency state occurs in women harboring heterozygous mutations in SLC30A2/ZnT2, which implies that a single gene copy of the wild type (WT) allele is not sufficient for the secretion of zinc into the milk to meet the infant's nutritional needs [32]. We have further reported that the frequency of individuals harboring TNZD causing alleles was as high as 1 in 2334 individuals from various ethnic groups [34]. Furthermore, the frequency of the specific founder p.G87R mutation in the Ashkenazi Jewish population was even higher and attained a striking frequency of 1 in 576 individuals (unpublished data); this frequent mutation is known to cause TNZD [29].…”
Section: Znt2 (Slc30a2) Mutations and Transient Neonatal Zinc Deficiementioning
confidence: 99%
“…If these findings also reflect the function of ZnT2 in women's mammary gland, it may negatively affect not only human milk composition, but also the actual breastfeeding ability. Importantly, these findings might explain the relatively low number of TNZD cases that were reported in the literature in contrast to the high frequency of TNZD causing alleles in the general population [34]. If women harboring loss of function (LoF) mutations in SLC30A2/ZnT2 also suffered from low milk supply, supplementary foods must be provided to the infant relatively early (i.e., baby formula) which will therefore mask the zinc deficiency in the milk.…”
Section: Znt2 (Slc30a2) Mutations and Transient Neonatal Zinc Deficiementioning
confidence: 99%